2017
DOI: 10.1016/j.jpeds.2017.05.056
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of Preterm Infants following Discussions about Withdrawal or Withholding of Life Support

Abstract: Objectives To describe the frequency of postnatal discussions about withdrawal or withholding of life-sustaining therapy (WWLST), ensuing WWLST, and outcomes of infants surviving such discussions. We hypothesized that such survivors have poor outcomes. Study design This retrospective review included registry data from 18 centers of the National Institute of Child Health and Human Development Neonatal Research Network. Infants born at 22–28 weeks of gestation who survived >12 hours during 2011–2013 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Notably, redirection of care does not always result in death; there is a possibility of survival, and survivors frequently have altered developmental trajectories. For the infants for whom redirection of care discussions occurred and who survived to hospital discharge, NDI and death after discharge previously were explored by James et al with a limited number of patients. NDI was more common among survivors for whom there were redirection of care discussions (51%) compared to survivors for whom there were no redirection of care discussions (15%; P < .001) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, redirection of care does not always result in death; there is a possibility of survival, and survivors frequently have altered developmental trajectories. For the infants for whom redirection of care discussions occurred and who survived to hospital discharge, NDI and death after discharge previously were explored by James et al with a limited number of patients. NDI was more common among survivors for whom there were redirection of care discussions (51%) compared to survivors for whom there were no redirection of care discussions (15%; P < .001) .…”
Section: Discussionmentioning
confidence: 99%
“…Redirection of care involves disengagement from one goal or set of goals, such as long-term survival, and reengagement with a new goal, such as making family memories . There is marked variability surrounding redirection of care, which is inclusive of withdrawal and withholding of life-sustaining treatment, across centers and across countries . Over time, attitudes and practices have shifted with respect to redirection of care for infants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations might address symptom assessment and management skills; studying commonly used, but poorly evaluated medications; looking further into the barriers and facilitators of PC in the NICU across staff/disciplines [ 28 , 29 , 30 , 31 , 39 , 44 , 45 ]; and evaluating effective communication strategies and decision-support for families and staff [ 46 , 47 ]. The utilization of large neonatal population databases to make inquiries and construct studies to answer common problems would seem to hold great potential [ 48 ]. What are the best ways to manage common symptoms?…”
Section: Discussionmentioning
confidence: 99%
“…3 The trajectory of these infants into early childhood and school age is unclear, as the impact of neonatal morbidities changes over time. 4,5 James et al, 6 through the National Institutes of Child Health and Development Neonatal Research Network (NICHD-NRN) provided new insight into a difficult practice in pediatrics, the withdrawal or withholding of life-sustaining therapy (WWLST), which typically coincides with end-of-life discussions in the intensive care unit. The study found that at NRN hospitals, these discussions occurred approximately 15% of the time for infants born at ≤28 weeks of gestation who survived until at least 12 hours of life.…”
Section: Threading the Needle For The Tiniest Babiesmentioning
confidence: 99%